The in vitro and in vivo anti-inflammatory and anti-oxidative effects of an amino acid blend supplemented feed on pigs experimentally challenged with Salmonella Typhimurium - Ham, Sehyeong; Suh, Jeongmin; Kim, Jieun; Gu, Min Jeong; Park, Min Ah; Oh, Eunseon; Moon, Jun-Ok; Chae, Chanhee (Frontiers in Veterinary Science, 2024)
Background The in vitro and in vivo anti-inflammatory and anti-oxidative effects of an amino acid (AA) blend (tryptophan, threonine, and methionine) in pigs. Objective This study aimed to evaluate the in vitro anti-inflammatory and anti-oxidative effects of an AA blend on intestinal porcine epithelial cells (IPEC-J2) and the in vivo anti-inflammatory and anti-oxidative effects in pigs experimentally challenged with Salmonella Typhimurium. Methods IPEC-J2 were pretreated with an AA blend for 25 h and then treated with lipopolysaccharide (LPS), deoxynivalenol (DON), or H2O2 for in vitro evaluation. A controlled standard diet supplemented with 0.3% of the AA blend was orally fed to the treated group pigs for 14 days, beginning at 21 days of age. At the end of the feeding period, pigs were orally inoculated with Salmonella Typhimurium. Results Pre-treatment with the AA blend reduced LPS/DON-induced interleukin (IL)-8 mRNA as a measurement of the anti-inflammatory effect and H2O2-induced reactive oxygen species (ROS) as a measurement of the anti-oxidative effect on IPEC-J2. Feeding with an AA blend resulted in a reduction of proinflammatory (tumor necrosis factor-α, IL-6, and IL-8) cytokine levels, while treated pigs experienced an increase in anti-inflammatory IL-10 cytokine in their sera. The addition of an AA blend-supplemented pig feed resulted in significantly lower Salmonella-induced cecal lesion scores compared to untreated pigs. Discussion Supplementation of feed with an AA blend reduced intestinal inflammation and pathology in pigs and may be applied for the control of Salmonella Typhimurium infection, as demonstrated in this study.